THE ANALYSIS OF INFAQ FUND ADMINISTRATION MASJID JOGOKARIYAN MANTRIJERON YOGYAKARTA IN ISLAMIC PERSPECTIVE - Sandiko Yudho Anggoro (Universitas Airlangga, 2018)
Masjid should be central of moslems actifities. But, fact in life a function of masjid just for pray or worship. One of masjid function that should not removed is masjid function as an infaq fund administator. A less managements and still manage by traditional way also a function of infaq fund does not running well, so is difficults to take control an infaq fund managements. In fact the fund from infaq, charity, and zakah are sourcess of islamic economy. Masjid Jogokariyan Jogjakarta is one of many masjid that generally have a function only as a worship place. This paper aimed to know a model of infaq managements in this masjid also how does a view of islamic law againts these managements in this masjid. This research is field research, data that required obtained from documentations and interview with responddents, Jogokariyan masjid council who directly related with an infaq fund managements. Data and informations that obtained from a field investigated with the analysis and testing back over all data or information that has been collected from the field. Results from this research is masjid fund come from anything about nafaqah like zakah, infaq, and charity. Fund managements like zakah come in masjid baitul maal, meanwhile voluntary nafaqah come in masjid fund. Next also a funtions of these two fund is differents by two, for obligatory nafaqah spent to eights class criteria that explaine in fiqih meanwhile voluntary nafaqah spent for all that society need and masjid dakwah. Also infaq fund managements in this masjid suitable so much with islamic laws that have done by our Prophet era that is a masjid as central of moslems economy.Key words: Infaq, Masjid, Managements